2023
DOI: 10.3390/nu15040867
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Pea Protein Intake Provides Sex-Specific Protection against Dyslipidemia in Offspring from Obese Pregnancies

Abstract: Increased consumption of dietary pulse protein has been shown to assist in body weight regulation and improve a range of metabolic health outcomes. We investigated if the exchange of casein for yellow pea protein (YPPN) in an obese-inducing maternal diet throughout pregnancy and lactation offered protection against obesity and dyslipidemia in offspring. Sixty female Sprague Dawley rats were fed a low-calorie control diet (CON), a high-caloric obesity-inducing diet (with casein protein (CP), HC-CP), or an isoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…This may be attributed to the limited impact of the intervention on maternal obesity. However, in a similar rat model, we have recently reported that the supplementation of an obesity-inducing maternal diet with yellow pea protein [30] and fiber [29] fractions throughout pregnancy improved the metabolic health of offspring independent of a change in maternal obesity status.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This may be attributed to the limited impact of the intervention on maternal obesity. However, in a similar rat model, we have recently reported that the supplementation of an obesity-inducing maternal diet with yellow pea protein [30] and fiber [29] fractions throughout pregnancy improved the metabolic health of offspring independent of a change in maternal obesity status.…”
Section: Discussionmentioning
confidence: 92%
“…Data were checked for normality using the Shapiro-Wilk test. Based on our previous work [30], we estimated the requirement of a sample size of 8 mothers/group (effect size, 1.49; power, 0.90; p < 0.05) to observe a 10% reduction in offspring body weight. Differences between treatments (with an individual rat as the experimental unit) were analyzed with a general linear model ANOVA with an LSD (least significance difference) post hoc test.…”
Section: Animals Diet and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic TG was extracted from frozen tissue and analyzed with a commercial kit (Zenbio, STG-1-NC) according to previously published work. 21…”
Section: Blood Biochemistrymentioning
confidence: 99%
“…44 Additionally, we recently reported that maternal consumption of a yellow-pea protein-supplemented diet throughout pregnancy and lactation protected against hepatic TG accumulation in male offspring. 21 Hence, the benefits of yellow peas with respect to hepatic steatosis are likely fraction-specific and the greatest potential benefits may be realized through consumption of whole yellow peas or by combining different yellow-pea fractions to obtain a specific desired metabolic effect. Interestingly, a recent longitudinal study in humans using multiple 24-h maternal pregnancy diet recalls and MRI assessment of hepatic fat in children (4-8 years old) reported that higher maternal fiber intake was associated with lower hepatic fat in offspring.…”
Section: Lipoprotein Sizementioning
confidence: 99%